2005
DOI: 10.1016/j.seizure.2005.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Visual function in epilepsy patients treated with initial valproate monotherapy

Abstract: The use of VPA in the treatment of epilepsy is not associated with visual field defects similar to vigabatrin, but may induce abnormalities in colour vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…With regard to use of additional AEDs, McCoy et al 15 detected a significantly higher percentage of retinal toxicity in a group of patients treated with vigabatrin in combination with other AEDs and questioned whether vigabatrin alone was responsible for the defects. However, in other studies, monotherapy with GABAergic drugs such as valproate 21 or tiagabine 22 did not cause VFDs. In the present study, two children treated with vigabatrin monotherapy had severe VFDs.…”
Section: Discussionmentioning
confidence: 82%
“…With regard to use of additional AEDs, McCoy et al 15 detected a significantly higher percentage of retinal toxicity in a group of patients treated with vigabatrin in combination with other AEDs and questioned whether vigabatrin alone was responsible for the defects. However, in other studies, monotherapy with GABAergic drugs such as valproate 21 or tiagabine 22 did not cause VFDs. In the present study, two children treated with vigabatrin monotherapy had severe VFDs.…”
Section: Discussionmentioning
confidence: 82%
“…49,50 One study reports a concentric visual field defect in a 22-year-old patient. 51 In contrast, Sorri et al 52 found that VPA therapy was not associated with visual field defects after 8.4 Ϯ 5.1 years of treatment. Furthermore, morphologic retinal alterations (modifications of retinal nerve fiber layer or macular thickness) have not been reported in patients after 1 year of VPA treatment.…”
Section: Discussionmentioning
confidence: 93%
“…[23] In a cross-sectional study involving 18 patients who had been taking valproate monotherapy for 2-20 years, only minor abnormalities in colour vision were discovered in two patients. [118] Short wavelength-sensitive cones seemed to be affected by the antiepileptic drug. This uncommon effect is mostly subclinical and does not require monitoring.…”
Section: Abnormal Colour Perceptionmentioning
confidence: 99%
“…Visual acuity, both subjective and objective, was preserved. [118] 7.9 Impaired Contrast Sensitivity…”
Section: Abnormal Colour Perceptionmentioning
confidence: 99%